Market-based governance in farm animal welfare - a comparative analysis of public and private policies in Germany and France - Vogeler, Colette Sophie (Animals, 2019)
The intensification of livestock production and the focus on economic gains of agricultural policy have resulted in animal welfare related challenges. In many countries the societal concern for the welfare of farmed animals is increasing. Whereas policymakers on the European Union’s level and in EU member states have passed specific farm animal protection laws, the existing policies do not always guarantee the welfare of farmed animals. At the same time, the engagement of market actors in the field is increasing. This article explores the development of public and private policies in two countries with very different levels of regulation. By conducting a comparative analysis of public and private policies in Germany and France, the findings illustrate that, although they have different starting points, retailers in both countries are getting increasingly involved in farm animal welfare. In addition, there is evidence that governmental policies are shifting from regulatory to voluntary approaches in cooperation with the private sector. Given that in both countries these dynamics are a very recent development, it remains to be seen whether governmental actors will (re-)assume the lead in the field, whether they will engage in cooperation with private actors, or whether they will leave the task of agricultural restructuring to the market.
Gesehen am 23.10.2019